2011
DOI: 10.1117/12.877763
|View full text |Cite
|
Sign up to set email alerts
|

Inspection and analysis of the walls of fluid filled tubes by active electrolocation: a biomimetic approach

Abstract: During their nocturnal activity period, weakly electric fish employ a process called "active electrolocation" for navigation and object detection. They discharge an electric organ in their tail, which emits electrical current pulses, called electric organ discharges (EOD). Local EODs are sensed by arrays of electroreceptors in the fish's skin, which respond to modulations of the signal caused by nearby objects. Fish thus gain information about the size, shape, complex impedance and distance of objects.Inspired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…However, the precise diagnosis and explicit characterization of plaques is still a big challenge in the medical field. The concept of a multielectrode electrolocation sensor based on the principle of active electrolocation of weakly electric fish for coronary diagnostics has been proposed before [1,2]. Weakly electric fish such as Gnathonemus petersii use Mormyromast electroreceptor organs to sense self emitted electrical signals (electric organ discharges, EOD) during active electrolocation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise diagnosis and explicit characterization of plaques is still a big challenge in the medical field. The concept of a multielectrode electrolocation sensor based on the principle of active electrolocation of weakly electric fish for coronary diagnostics has been proposed before [1,2]. Weakly electric fish such as Gnathonemus petersii use Mormyromast electroreceptor organs to sense self emitted electrical signals (electric organ discharges, EOD) during active electrolocation.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to use active electrolocation to determine the conductivity and the dielectric properties of coronary plaques with a multi-electrode sensor and thus characterize different plaque types. Our previous studies have shown [1,2] that it is possible to differentiate the material properties and different size of the targets with commercially available four-electrode catheter sensors based on the electrolocation principle. In this paper, we introduce a novel design of a multi-electrode catheter sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, we have already explained the physical phenomenon of an active electrolocation sensor catheter measuring within an insulating tube [3][4][5]. In these previous experiments, glass tubes were used instead of Plexiglas tubes.…”
Section: Experimental Results and Finite Element Modeling Datamentioning
confidence: 98%
“…After validating the modeled data, we analyzed the effect of the sender to receiver distance on localization parameters of the electrical image. Our earlier studies showed that the sender to receiver distance is a significant parameter for extracting data from the electric images [3][4][5]. When the sensor was moved inside the glass or Plexiglas tube in the aquatic bath, a first peak is observed when the sender approaches the target.…”
Section: Modeling and Simulationmentioning
confidence: 98%
See 1 more Smart Citation